A novel function of IL-33: suppression of innate antiviral immunity - Matsuda, Akio (Journal of Thoracic Disease, 2016)
Asthma is a chronic type 2 inflammatory disease of the airways that is pathologically characterized by persistent structural changes in the airway walls, including goblet cell hyperplasia, thickening of the basement membrane, smooth muscle cell hypertrophy/hyperplasia, increased deposition of extracellular matrix proteins, and abnormally excessive vasculature (1). These structural changes are collectively described as airway remodeling, which causes loss of lung function due to irreversible airflow obstruction, airway hyperreactivity and corticosteroid refractoriness (2). Importantly, structural abnormalities due to airway remodeling are already present in childhood asthma (3).